Online Purchasing Model for PwD (People with Disabilities) Consumers: Pre and Post Disability Behaviors - Sefa Emre Yilmazel (SAGE Open)
People with Disabilities (PwD) is discussed in the literature as the largest minority in the world. This group generally prefers online shopping instead of store shopping due to the physical difficulties they experience. However, no online shopping model has been developed for this group. Therefore, the aim of this study is to reveal an online purchasing model for PwDs in line with the theory of planned behavior. In this regard, the effects of the variables perceived ease of use, perceived usefulness, peer communication, security concern, privacy concern and physical disabilities on consumers’ purchasing intention and subsequent purchasing behavior through subjective norms, attitude and behavioral control were investigated with pre- and post-disability data. In the study, data was collected from participants before (322) and after (546) disability. As a result of this study, it was revealed that online behavior of consumers before and after the disability differed. Especially peer communication made a significant difference in purchasing behavior after the disability. Consumers became more sensitive about security and privacy in their online shopping after the obstacle. In addition, consumers’ perceived usefulness had a significant effect on their attitudes after the disability. Therefore, as a result of the study, an online shopping model for PwD consumers was created.